Personal Dignity as a Limit for Transhumanism (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
This text explores the question of the possible limits of transhumanism. However, unlike others, it does not focus on moral or ethical limitations, nor on technological or biological limitations. It deals, in particular, with its ontological and anthropological boundaries. The reflection that develops warns about the personal tenor of the subject and his dignity, involved in transhumanism. This note of the subject is unalterable and remains in the midst of the possible changes or transformations that transhumanism poses.